Remote sensing-based assessment of four decades of land use/land cover change in the Sigi River Watershed, East Usambara Mountains, Tanzania - Chidodo, Simon; Zhang, Lulu; Zarei, Azin; Feger, Karl-Heinz (Frontiers in Remote Sensing, 2025)
Introduction:Agricultural expansion and intensification have driven substantial land use/land cover (LULC) changes. These changes have caused a drastic reduction in ecosystem services. Understanding the spatial and temporal patterns of LULC change in relation to topographic attributes is essential for effective watershed management, as it provides insights into landscape heterogeneity and supports evidence-based conservation planning. This study analyzed LULC dynamics from 1983 to 2022 in the Sigi River watershed (887 km2) in the East Usambara Mountains, a biodiversity hotspot and critical water source in northeastern Tanzania.Methods:Multi-temporal Landsat satellite images were classified using the Random Forest algorithm to assess LULC transitions across elevation and slope gradients.Results:The results revealed marked variations in LULC change across topographic zones. The foothill and escarpment areas experienced extensive deforestation and the rapid expansion of small-scale cultivation, whereas upland areas exhibited relatively lower levels of change, primarily transitioning from forest to spice agroforestry. These spatial patterns reflect the influence of population pressure, socio-economic transformations, government land policies, and the establishment of protected areas in the uplands. Slope steepness further modulated LULC dynamics, with steeper slopes across all elevations showing notable forest loss, while gentler slopes may have undergone earlier land conversion, preceding the study period.Discussion:The study underscores the importance of integrating topographic attributes into LULC assessments to better understand landscape transformation processes and support sustainable land-use planning and watershed management.